(untitled) (Global Media Journal - German Edition, 2013)
On June 14th, 2013, Iranians headed to the polls to cast their votes for the country’s next president. The unexpected turnout, that followed months of debates between those who wanted to go back to ballot boxes and those who did not, resulted in the election of Hasan Rouhani, the moderate cleric. About three months after the election, in his interview with NBC NEWS, Mr. Rouhani explained social networks’ role in his victory as undeniable and appreciated his supporters for promoting his campaign on these platforms. This commentary reviews Rouhani’s and the other state candidates’1 use of formally blocked social networks during the recent presidential election in Iran, as a very recent shift toward planned and targeted use of social media by the government.